Several New Aspects of the Foraging Behavior of Osmia cornifrons in an Apple Orchard - Shogo Matsumoto; Tsutomu Maejima (Psyche: A Journal of Entomology)
We investigated the foraging behavior of Osmia cornifrons Radoszkowski, which is a useful pollinator in apple orchards consisting of only one kind of commercial cultivars such as “Fuji”, and of different types of pollinizers, such as the red petal type, “Maypole” or “Makamik”. It was confirmed that, in terms of the number of foraging flowers per day, visiting flowers during low temperatures, strong wind, and reduced sunshine in an apple orchard, O. cornifrons were superior to honeybees. We indicated that O. cornifrons seemed to use both petals and anthers as foraging indicator, and that not only female, but also males contributed to apple pollination and fertilization by the pollen grains attached to them from visiting flowers, including those at the balloon stage. It was confirmed that O. cornifrons acts as a useful pollinator in an apple orchard consisting of one kind of cultivar with pollinizers planted not more than 10 m from commercial cultivars.